Inuit songs from Eskimo Point - Amarook, Lucy; Suluk, Luke; Pelinski, Ramón Adolfo (Book collections on Project MUSE., 1979)
41 songs recorded in Spring 1977 which document the traditional genres of the ajajait, of the animal songs and of the children's game songs. Includes words, in syllabics and translated, and music.